Morfofisiologi Ratun Padi Sistem Tanam Benih Langsung di Lahan Pasang Surut - Mareza, Evriani; Djafar, Zainal Ridho; Suwignyo, Rujito Agus; Wijaya, dan Andi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTThe morphophysiology of ratoon is different from the main plant of rice and was influenced by location and cultivation.This research was intended to evaluate morphophysiology characters of rice ratoon planted by direct seeding system in tidal swamp at various stubble cutting height. The experiment was conducted in November 2013-April 2014 at tidal swamp overflow type B in Telang Sari Village, District of Tanjung Lago, Banyuasin, South Sumatra Province. The experiment used randomized block design with 5 replications. Treatment was stubble cutting height 10, 20, 30, 40 and 50 cm above the soil surface. Rice was planted at 4 m x 5 m plot, the distance between plot 1 m. Data were analyzed by test of variance and 5% HSD test. Morphophysiological characters of rice ratoon were influenced by stubble cutting height. Cutting height of 20-40 cm above soil surface increased the ratoon number of tillers per hill, leaf area per hill, dry weight per hill, percentage of empty grains per panicle, grain weight per hill and percentage ratoon/main crop production per hill. The higher stubble cutting, the lower the number of leaves per tiller, leaf area per tiller, carbohydrate content, and number of grains per panicle of ratoon, however it accelerated age of flowering and harvesting. Keywords: direct seeding system, ratoon system, rice growth and production, stubble cutting height